The Influence of Cognitive Style on Abstraction Ability and Mathematical Problem-Solving in Problem-Based Learning - Habeahan, Winmery Lasma; Malik, Meilisa; Firdaus, Muhammad Huda; Panjaitan, Arie Candra (ALACRITY : Journal of Education, 2025)
This article explores the influence of cognitive style on abstraction ability and mathematical problem-solving skills in Problem-Based Learning (PBL). Cognitive style, which reflects how individuals process and organize information, is hypothesized to play a significant role in determining students' success in understanding abstract concepts and solving mathematical problems. This study employs a quantitative method involving secondary-level students as participants. The research instruments include cognitive style tests, abstraction ability tests, and mathematical problem-solving tests. The results indicate that students with an analytical cognitive style tend to have higher abstraction abilities and better performance in mathematical problem-solving compared to those with a holistic cognitive style. These findings suggest that cognitive style influences the effectiveness of problem-based learning, particularly in subjects requiring logical and abstract thinking, such as mathematics. The implications of this research highlight the importance of educators recognizing and accommodating the diversity of students' cognitive styles when designing learning strategies. Furthermore, the study suggests the need to develop more flexible and inclusive learning approaches to maximize each student's learning potential. This article contributes to understanding how individual factors, such as cognitive style, can influence learning outcomes, particularly in the context of PBL.